Work from Home: Social Media, Virtual Meeting and the New Family Relationship - Mohammad Jacky; FX Sri Sadewo; Sugeng Harianto; Arief Sudrajat; Mansor Mohd Noor; Des Fenoughty (The Journal of Society and Media, 2021)
The COVID-19 pandemic has actually forced people to work at home. Office activities outside the home can result in the transmission of COVID-19 to its workers. The government has taken a decision to minimize employee attendance at the office. Employees are encouraged to work at home (WFH), especially in groups vulnerable to infection. The house is turned into an “office space.” With the internet network, these employees are connected to each other. Although factually, this pattern is not a new thing because it has been carried out since the 2000s and is now becoming increasingly intensive. Through qualitative research with an ethnomethodological perspective, the results show that with this pattern, the house has become an encounter between public space and domestic space. This requires a strategy to manage roles in the home. Through in-depth observations and interviews, there were several important findings. First, there is a struggle for space in the house. Second, there is a transfer of stress from work to home. Third, there is a renegotiation of roles in the house, so as not to disturb family harmony. No less important, the community of users of social media and virtual meetings builds constructions of public and domestic space and time. The division of space and time in virtual space is also related to a person's role and social status when in the real world of work.